TINJAUAN TEKSTUAL DAN KONTEKSTUAL ANALISIS LIRIK LAGU KALA CINTA MENGGODA KARYA GURUH SOEKARNO PUTRA - Anang Sudigdo (Sasindo, 2015)
ABSTRACTThe purpose of the research is to describe (1) Aspects of grammatical which isused to the lyric of song Kala Cinta Menggoda written by Guruh Soekarno Putra. (2)Aspects of lexical which is used to the lyric of song of Kala Cinta Menggoda written byGuruh Soekarno Putra. This reasearch used qualitative descriptive method. The sourcesof data are transcript and the recorded of the poppuler lyric song of Kala CintaMenggoda written by Guruh Soekarno Putra. Technique of collecting data usedscrutinized, noted, and content analysis to interpret the meaning of message in thelyrics of the song. Based on the analysis of the research data, it can be concluded (1)Grammatical aspects which are used on song lyric Kala Cinta Menggoda by GuruhSoekarno Putra are: (a) the reference including the first pronoun, the first singglepronoun sticked on right, the first single pronoun sticked on left, the second single freepronoun, the second single pronoun sticked on right, (b) substitution, (c) elliptycalsentences, (d) conjunction. (2) Lexicalaspects which are used on song lyric Kala CintaMenggoda by Guruh Soekarno Putra are: (a) repetition including completed, greetingrepetition, and epizeuksis repetition, (b) synonim, (c) antonym. (3) Contextual the songlyric Kala Cinta Menggoda by Guruh Soekarno Putra can be understood by principle ofpronoun interpretation.Keyword: textual aspect, contextual aspect, grammatical aspect, and lexical aspect.